Energising students in learning English as a second language / Noridah Sain, Hema Roshmy Mustafa and Dr. Norazman Abdul Majid - Sain, Noridah; Mustafa, Hema Roshmy; Abdul Majid, Norazman (2011)
This study investigates learners' perceptions of kinesthetic learning activities (KLA) used to teach English as a second language in secondary level. Using mixed method research design, with surveys and interviews, this research which is mainly qualitative and descriptive in nature presents students' perceptions towards KLA so as to promote active learning environments. The findings showed that KLA averted monotony, eliminated stress and encouraged social interaction in an enjoyable and active learning atmosphere. The study also discovered that the subjects equated kinesthetic learning activities to learning processes which would encourage fun learning experiences.